1986
DOI: 10.1111/j.1744-7348.1986.tb01976.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between fungicide, plant growth regulator, nitrogen fertiliser applications, foliar disease and yield of winter barley

Abstract: SUMMARYLeaf size and foliar disease in winter barley increased with increasing total amounts of nitrogen applied to the crop: flag leaf areas increased at an average of 10% per 35 kg N ha‐1 Nitrogen top dressing applied in mid‐March (G.S. 31) resulted in larger leaves, more foliar disease, more straw, delayed ear emergence, fewer grains ear‐1 and less grain yield than nitrogen applied in mid‐April (G.S. 31). Application of chlormequat at G.S. 30 gave a variable response, but overall it increased fertile stems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

1986
1986
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…Experiments on winter barley in south-west England since 1981 (Jordan et ai, 1985;Jordan & Stinchcombe, 1986a, 1986b, 1988, characterized and quantified the effects and interactions of three major input variables in winter barley production. They also showed that postponing the main N dressing until mid-April can reduce both the risk from fungal diseases and the need for fungicide sprays to maintain yield and quality.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments on winter barley in south-west England since 1981 (Jordan et ai, 1985;Jordan & Stinchcombe, 1986a, 1986b, 1988, characterized and quantified the effects and interactions of three major input variables in winter barley production. They also showed that postponing the main N dressing until mid-April can reduce both the risk from fungal diseases and the need for fungicide sprays to maintain yield and quality.…”
Section: Discussionmentioning
confidence: 99%
“…found positive yield responses of barley cultivars to Tilt application independent of resistance or susceptibility to net blotch. Johnston and Macleod (1987) found Jordan and Stinchcombe (1986) reported an increase. Floret fertility may be affected by treatments that affect assimilation (Fischer and Stockman 1980).…”
Section: Economicsmentioning
confidence: 99%
“…En outre, ses effets sur la hauteur de la paille, sur le nombre de talles viables de la hauteur de la paille, du nombre de talles viables par mbtre carre et de grains par 6pi, mais la teneur en protdine du grain n'a 6t6 augment6e qu'une seule ann6e (1988 Jordan and Stinchcombe (1986) and Zebarth and Sheard (1991) found that increased Nfertilization increased the severity of foliar diseases because of lush vegetative growth.…”
unclassified
“…Lodging of cereal crops may be reduced by various means such as plant growth regulators or by breeding. In winter barley, however, effects of growth regulators depend to a great extent on favourable environmental conditions (Jordan & Stinchcombe, 1986). Adding a resistant component to a lodging-susceptible cultivar might be an inexpensive and more reliable way to reduce lodging.…”
Section: Introductionmentioning
confidence: 99%